Effect of Biodegradable Mulch and Different Synthetic Mulches on Growth and Yield of Field-Grown Small-Fruited Tomato (Lycopersicon esculentum Mill.) - Katarzyna Adamczewska-Sowińska; Joanna Bykowy; Janina Jaworska (Agriculture)
Mulching is a widely adopted practice in vegetable cultivation globally. This technique employs various plastic materials, such as polyethylene (PE) film or polypropylene (PP) nonwoven fabric, with an increasing trend toward the use of biodegradable materials. Between 2014 and 2016, field experiments were conducted to evaluate the performance of the small-fruited tomato Intrigo F1 cultivated using synthetic mulches. The trials, designed as single-factor experiments employing a randomized block layout with three replicates, assessed plant morphological traits, yield, and the biological value of the tomato fruits. Weather conditions and the type of mulch applied had a pronounced influence on the quality of tomato plants and yield. Compared to the control, the use of black, red, and aluminum PE films and brown PP resulted in a 7.2% increase in plant height. All mulching treatments, except white film, increased the lateral spread of the plants by an average of 24.2%. Plants cultivated on red PE film exhibited a 26.4% increase in leaf count with respect to the control. Mulched treatments achieved an average increase of 19.6% in marketable yield. The highest marketable fruit yield was recorded with black nonwoven fabric mulch. Mulching had a significant effect on the chemical composition of tomato fruits. Fruits on biodegradable foil had the most potassium, lycopene, and polyphenols.